Internet-Based Interventions for the Prevention and Treatment of Mental Disorders in Latin America: A Scoping Review - Jiménez-Molina, Álvaro; Franco, Pamela; Martínez, Vania; Martínez, Pablo; Rojas, Graciela; Araya, Ricardo (Frontiers in Psychiatry, 2019)
Background: There is a huge gap in the treatment of mental disorders in Latin America, especially among socioeconomically disadvantaged groups. Given the sharp increase of Internet access and the rapid penetration of smartphones in the region, the use of Internet-based technologies might potentially contribute to overcoming this gap and to provide more widely distributed and low cost mental health care in a variety of contexts. Methods: We conducted a scoping review of the literature in order to systematically map the existing evidence on use of Internet-based interventions for prevention, treatment and management of mental disorders across Latin American countries, as well as to identify existing gaps in knowledge. Six electronic databases were searched for published papers (PubMed, Embase, CINAHL, Web of Science, SciELO and CENTRAL). Results: After the eligibility assessment, we identified 22 Internet-based studies carried out in Latin America for prevention, treatment, education, or facilitating self-management of mental disorders. Included studies mainly targeted depression (n=11), substance misuse (n=6), anxiety (n=3), and mental health literacy for education and health professionals (n=2). Most studies were undertaken in Brazil (n=6), Mexico (n=5), and Chile (n=4). Only three studies were randomized controlled trials (RCTs), four were pilot RCTs and fifteen were naturalistic, acceptability, or feasibility studies. The three RCTs identified showed disparate results but overall there are challenges to face. Better results are seen in the short-term (post-intervention or after three months), but most studies do not explore outcomes for long enough (follow-up after six or 12 months). Most of the feasibility and pilot studies showed reasonably good acceptability for a wide range of strategies but difficulties to engage and retain participants for long enough or adhering to established protocols. Conclusion: This study shows that Internet-based interventions for the prevention and treatment of mental disorders are growing rapidly in Latin America, but there are few studies on effectiveness and cost-effectiveness, making it difficult to provide the evidence needed to justify scaling up these interventions.